Deep inelastic scattering structure functions of holographic spin-1 hadrons with N f ≥ 1 - Koile, Leandro Ezequiel (2014)
Two-point current correlation functions of the large N limit of supersymmetric and non-supersymmetric Yang-Mills theories at strong coupling are investigated in terms of their string theory dual models with quenched flavors. We consider non-Abelian global symmetry currents, which allow one to investigate vector mesons with N f > 1. From the correlation functions we construct the deep inelastic scattering hadronic tensor of spin-one mesons, obtaining the corresponding eight structure functions for polarized vector mesons. We obtain several relations among the structure functions. Relations among some of theirmoments are also derived. Aspects of the sub-leading contributions in the 1/N and N f /N expansions are discussed. At leading order we find a universal behavior of the hadronic structure functions.